Research on Urban Historical Block Planning Method Based on Big Data Multimedia Technology. (29th September 2022) - Yang, Mulan; Afla, Mohamad Reza Bin Mohamed
Abstract : With the application and popularization of big data technology, it is more advantageous than traditional urban planning to use big data multimedia technology to reasonably plan the historical blocks of the city. The protection and renewal of historical and cultural blocks have become the core elements to improve the quality of urban development and promote the development of "people-oriented" new urbanization. We analyze and study the planning methods of urban historical blocks under the big data technology. This paper analyzes the different values of historical blocks. By comparing the division effect and business operation mode of historical blocks under different technological environments, it is concluded that the efficiency of traditional data survey and statistical mode is faster than that of big data multimedia technology, and it is more accurate and efficient in analyzing and studying the commercial market and tourism development planning of historical blocks. Through big data multimedia technology data query, we have mastered the cultural connotation of the historical district, protected the historical environment, excavated the historical culture, activated the vitality of the district, and optimized the district environment. It provides convenient scientific and technological means for the protection and development planning of cultural heritage such as historical blocks in China.